2015
DOI: 10.2174/1566524015666151026105123
|View full text |Cite
|
Sign up to set email alerts
|

The physics for the formation of cell-in-cell structures.

Abstract: The formations of cell-in-cell structures have been found in several important biological processes. Recent studies have shed light on the biochemical signaling pathways as well as the quantitative understandings of the underlying physics. Multiple new features that regulate the cellular engulfment have been identified. However, the driving forces promoting the structural formation are still under debate. This review focuses on the recent progress and discusses the potential significance of the existing physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Whereas, heterogeneities within tumor clones drive CIC formation, the process has been shown to be complex and genetically controlled (19). E-cadherin-mediated adherens junctions bring cells together, and set up asymmetric RhoA activity to drive cell internalization (8,9) with the assistance of optimal membrane cholesterol and lipids (20) and the inflammatory cytokine IL-8 (21).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, heterogeneities within tumor clones drive CIC formation, the process has been shown to be complex and genetically controlled (19). E-cadherin-mediated adherens junctions bring cells together, and set up asymmetric RhoA activity to drive cell internalization (8,9) with the assistance of optimal membrane cholesterol and lipids (20) and the inflammatory cytokine IL-8 (21).…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, via internalizing and killing the less fit “loser” tumor cells, and endowing aneuploidy to the progenies of outer “winner” tumor cells ( 2 , 3 ), CIC formation could serve as a mechanism of cell competition to promote clonal selection and therefore tumor evolution ( 4 ). Based on recent research on entosis, a CIC-mediated nonapoptotic cell death process ( 5 ), the mechanisms underlying formation of homotypic CICs between cells of epithelial origin are starting to be revealed ( 6 ). Current research fits a working model of two core elements: first, adherens junction, mediated by epithelial complexes formed by E- or P-cadherin and multiple essential catenins ( 7 , 8 ), brings cells together and sets up asymmetric RhoA activity by junction localized-p190A RhoGAP.…”
Section: Introductionmentioning
confidence: 99%
“…Current research fits a working model of two core elements: first, adherens junction, mediated by epithelial complexes formed by E- or P-cadherin and multiple essential catenins ( 7 , 8 ), brings cells together and sets up asymmetric RhoA activity by junction localized-p190A RhoGAP. Then, activated RhoA/ROCKs signaling drives actomyosin contraction and the following cell internalization ( 6 ). Besides, glucose starvation and membrane cholesterol/lipids were found important regulators of entotic CIC formation probably by affecting the phosphorylation of myosin light chain (MLC) ( 9 , 10 ), suggesting CIC formation is a complex and finely controlled process.…”
Section: Introductionmentioning
confidence: 99%
“…Latest researches indicated that cell-in-cell formation by entosis is a key mechanism of cell competition to promote clonal selection and tumor evolution [4244]. Despite being reported over a century, cell-in-cell remains largely mysterious in its forming mechanisms although progress were made recently [4547]. Since blocking CD47 by antibodies could efficiently induce macrophage-mediated phagocytosis of tumor cells and treat cancers, it would be interesting to examine whether CD47 also participate in cell-in-cell formation between tumors, and if so, would blocking CD47 a feasible way to inhibit tumor growth by inducing cell-in-cell formation and the mediated-cell death?…”
Section: Discussionmentioning
confidence: 99%